Identification of the Key Parameters for Electric Waterjet Intake Optimization - de Ribot Grau, Lleo; Vichanphruek, Nuttarat (My University, 2022)
Waterjets are commonly used in high-speed crafts because they have better propulsive efficiency compared to conventional marine propellers at high speeds. Nowadays, electric propulsion has been developed worldwide. This brings up the possibility of doing more research on how it can affect the hydrodynamic performance of the waterjet propulsion system. The main objectives of this project are to optimize the waterjet intake, which can maximize the overall system performance, and to investigate the hydrodynamic performance of the entire system when some constraints can be modified due to waterjet electrification. During this research, finding the system performance curve, the effect of extending pump-intake connection study, the effect of shaft removal study, rim-driven impeller study, and intake optimization are carried out. The results show that the intake design and the rotor driving method are directly related to the system efficiency because the inflow to the pump is significantly affected by the intake shape and the shaft. The impeller and the intake should be designed together to match the blades with the specific wake field. To achieve a better inflow to the pump, the key approaches are to lower the intake height and extend the cylindrical part of the intake ahead of the impeller.
Keywords: Waterjet; Optimization; Computational Fluid Dynamics (CFD); STAR CCM+; Capture Area; CAESES; Parameterized geometry; Wake field; Pump Performance